Peluang dan Tantangan Implementasi Nilai-Nilai Pancasila melalui Pemanfaatan Microsoft Copilot dalam Pembelajaran di Era Digital - Muhammad Anggie Farizqi Prasadana; Farhan Akbar; St. Zahwa (International Journal of Studies in International Education, 2024)
Currently, technology is experiencing rapid development, especially in the field of artificial intelligence (AI). One of the famous AIs is Microsoft Copilot. This artificial intelligence can be used to implement Pancasila values in learning. This research uses a qualitative research method of the literature study type. The results of the study show that there are opportunities and challenges in using Microsoft Copilot in the implementation of Pancasila values during the learning process in the digital era.